Did I say ‘pup’ or ‘pub’? An analysis of foreign language learners’ phonological self-awareness - Souza, Hanna Kivistö de; Lintunen, Pekka (Journal of Speech Sciences, 2023)
Language users possess knowledge about the second language (L2) phonological system and their own L2 pronunciation, known as phonological awareness and phonological self-awareness, respectively. Higher awareness about the L2 phonology has been shown to be beneficial for L2 pronunciation accuracy (e.g. Kennedy & Trofimovich, 2010), making it relevant to know which features L2 learners are able to notice and how the L2 phonology can be brought into the learners’ attention better. The aim of the paper is to examine language learners’ awareness about their own pronunciation by investigating which L2 segmental features are noticed, how one’s intelligibility is perceived and how participants view their phonological self-awareness abilities. 33 L1 Finnish learners of English enrolled in an English phonetics and phonology course recorded a speech sample and later listened to it by noting down the perceived pronunciation deviations on selected features. The participants also answered a phonological self-awareness questionnaire. The results indicate that the learners noticed segmental deviations in their productions, mainly in relation to consonantal voicing and vowel duration. The participants also perceived themselves as highly intelligible and reported it to be easy to notice the gap in their pronunciation, to identify pronunciation deviations in other speakers’ speech and to identify Finnish-accented English. Nevertheless, the overall verbalization of noticing was scarce and the participants manifested difficulties in explaining the noticed phenomena. The discussion relates the phonological self-awareness findings to pedagogical applications.